Characterizing the avian gut microbiota: membership, driving influences, and potential function - Waite, David W.; Taylor, Michael W. (Frontiers in Microbiology, 2014)
Birds represent a diverse and evolutionarily successful lineage, occupying a wide range of niches throughout the world. Like all vertebrates, avians harbour diverse communities of microorganisms within their guts, which collectively fulfil important roles in providing the host with nutrition and protection from pathogens. Although many studies have investigated the role of particular microbes in the guts of avian species, there has been no attempt to unify the results of previous, sequence-based studies to examine the factors that shape the avian gut microbiota as a whole. In this study, we present the first meta-analysis of the avian gut microbiota, using 16S rRNA gene sequences obtained from a range of publicly available clone-library and amplicon pyrosequencing data. We investigate community membership and structure, as well as probe the roles of some of the key biological factors that influence the gut microbiota of other vertebrates, such as host phylogeny, location within the gut, diet and association with humans. Our results indicate that, across avian studies, the microbiota demonstrates a similar phylum-level composition to that of mammals. Host bird species is the most important factor in determining community composition, although sampling site, diet and captivity status also contribute. These analyses provide a first integrated look at the composition of the avian microbiota, and serve as a foundation for future studies in this area.